Genetic variants in immune-related pathways and breast cancer risk in African American women in the AMBER consortium - Hong, Chi-Chen (Cancer Epidemiol Biomarkers Prev, 2018)
BACKGROUND: Constitutional immunity shaped by exposure to endemic infectious diseases and parasitic worms in Sub-Saharan Africa may play a role in the etiology of breast cancer among African American (AA) women. METHODS: A total of 149,514 gene variants in 433 genes across 45 immune pathways were analyzed in the AMBER consortium among 3,663 breast cancer cases and 4,687 controls. Gene-based pathway analyses were conducted using the adaptive rank truncated product statistic for overall breast cancer risk, and risk by estrogen receptor (ER) status. Unconditional logistic regression analysis was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for single variants. RESULTS: The top pathways were Interleukin Binding (p=0.01), Biocarta TNFR2 (p=0.005), and Positive Regulation of Cytokine Production (p=0.024) for overall, ER+, and ER− cancers, respectively. The most significant gene was IL2RB (p=0.001) for overall cancer, with rs228952 being the top variant identified (OR=0.85, 95% CI: 0.79-0.92). Only BCL3 contained a significant variant for ER+ breast cancer. Variants in IL2RB, TLR6, IL8, PRKDC, and MAP3K1 were associated with ER− disease. The only genes showing heterogeneity between ER− and ER+ cancers were TRAF1, MAP3K1, and MAPK3 (p≤0.02). We also noted genes associated with autoimmune and atopic disorders. CONCLUSIONS: Findings from this study suggest that genetic variants in immune pathways are relevant to breast cancer susceptibility among AA women, both for ER+ and ER− breast cancers. IMPACT: Results from this study extend our understanding of how inherited genetic variation in immune pathways is relevant to breast cancer susceptibility.